PdTe2 Transition‐Metal Dichalcogenide: Chemical Reactivity, Thermal Stability, and Device Implementation. (18th November 2019) - D'Olimpio, Gianluca; Guo, Cheng; Kuo, Chia‐Nung; Edla, Raju; Lue, Chin Shan; Ottaviano, Luca; Torelli, Piero; Wang, Lin; Boukhvalov, Danil W.; Politano, Antonio
Abstract: Palladium ditelluride (PdTe2 ) is a novel transition‐metal dichalcogenide exhibiting type‐II Dirac fermions and topological superconductivity. To assess its potential in technology, its chemical and thermal stability is investigated by means of surface‐science techniques, complemented by density functional theory, with successive implementation in electronics, specifically in a millimeter‐wave receiver. While water adsorption is energetically unfavorable at room temperature, due to a differential Gibbs free energy of ≈+12 kJ mol −1, the presence of Te vacancies makes PdTe2 surfaces unstable toward surface oxidation with the emergence of a TeO2 skin, whose thickness remains sub‐nanometric even after one year in air. Correspondingly, the measured photocurrent of PdTe2 ‐based optoelectronic devices shows negligible changes (below 4%) in a timescale of one month, thus excluding the need of encapsulation in the nanofabrication process. Remarkably, the responsivity of a PdTe2 ‐based millimeter‐wave receiver is 13 and 21 times higher than similar devices based on black phosphorus and graphene in the same operational conditions, respectively. It is also discovered that pristine PdTe2 is thermally stable in a temperature range extending even above 500 K, thus paving the way toward PdTe2 ‐based high‐temperature electronics. Finally, it is shown that the TeO2 skin, formed upon air exposure, can be removed by thermal reduction via heating in vacuum. Abstract : The chemical and thermal stability of PdTe2 is assessed by experiments and theory, with successive implementation in electronics. Remarkably, the responsivity of a PdTe2 ‐based millimeter‐wave receiver is 13 and 21 times higher than similar devices based on black phosphorus and graphene in the same operational conditions, respectively. Moreover, the PdTe2 surface is stable for one year, with only a sub‐nanometric TeO2 skin formed after air exposure.